Desain Strategi Pengelolaan Lahan Sebagai Upaya Pencegahan Kasus Korupsi - Fatihatul Izzah, Izzah (Siyasah Wa Qanuniyah, 2024)
Transparent and accountable land management is crucial in preventing corruption cases that harm society and hinder sustainable development. This article discusses design strategies that can be applied in land management to reduce the risk of corruption. The problem formulation includes identifying weaknesses in the land management system that are vulnerable to corrupt practices, developing effective land management strategies, and integrating these strategies with other anti-corruption efforts. The research questions include effective design strategies to mitigate corruption risks and evaluate their implementation. The research methodology uses a qualitative approach, with case studies and literature reviews on various land management strategies in different geographical contexts. The research findings indicate that strategies involving active public participation, the use of information technology for better monitoring, and strengthening internal oversight mechanisms can effectively reduce corruption incidents. Emphasizing transparency in policies and decision-making processes is also a key factor in ensuring the integrity of land management. This article contributes to both practical and theoretical understanding of how land management design strategies can play a significant role in preventing corruption.